Fa’aliyah Istikhdam Thoriqah ECOLA (Extending Concept Through Language Activities) Litahsin Maharat Al-Qira’ah Ladaa Tullaab Al-Fasl Al-Hadi A’syir fii Madrasah Tsanawiyah Islamiyah Hukumiyah 1 Pasaman - Hidayati, Hidayati; Rizal, Eka; Arsya, Fajriyani; Hasanah, Nur (Uktub: Journal of Arabic Studies, 2024)
The research starts from the problems faced at the Islamic State High School 1 Pasaman. The problem with this research is that they are unable to understand reading material, have difficulty understanding reading, do not pay attention to education, need to use various strategies in education, students' results in Arabic are less than the completion of the minimum acute (KKM) of 78.  is the aim of this study to find out the use of the ECOLA method to improve the reading skill of eleventh grade students majoring in religion. This quantitative research, quantitative research methodology is a research method based on a positivist philosophy and this research is used to investigate a particular community or intention. The experimental design used is Quasi Experimental Design and data analysis using the SPSS 26 software. As for the results of the research, the researcher decided that the different degree of the two chapters, so that t- arithmetic means -1.714, with the result of degrees of freedom (df)= 50 with a value of 5% is 2.008. If t-arithmetic means -1.714, less than t-table means 2.008, so the null hypothesis (Ho) is acceptable and the substitute hypothesis (Ha) is rejected. Its conclusion is that there is no effectiveness in using the method ECOLA to improve the reading skills of students in the eleventh-grade majoring in religion at the Islamic Government High School 1 Pasaman.